Implementasi Aplikasi Pengelolaan Data Transaksi Penjualan Berbasis Desktop (Studi Kasus: CV. Lian April Purbalingga) - Dina Mitasari; Khalimaturofi’ah Khalimaturofi’ah; Yuniar Laeli N.F (Journal Of Informatics And Busisnes, 2025)
This research discusses the design and development of a desktop-based data management application at CV. Lian April Purbalingga, a company engaged in sales and product distribution. The main problems faced by the company include manual recording of sales transactions, inventory management, and report generation, which often lead to errors and delays. The purpose of this study is to design an information system capable of managing data efficiently, with role-based access control between administrators and the owner to enhance data security. The software development method used in this research is the Waterfall model, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. Data were collected through observation, interviews, and literature studies, while system testing was conducted using Black Box Testing and user satisfaction surveys based on the Likert scale. The test results indicate that all system features function properly, and the user satisfaction survey shows an average score of 4.39 out of 5, which falls under the “Good” category. These results demonstrate that the developed desktop application effectively improves work efficiency, accelerates service performance, and minimizes errors in sales data recording.